Penerapan Prinsip Good Governance dalam Penyelenggaraan Pemerintahan Desa di Desa Oetuke, Kecamatan Kolbano, Kabupaten Timor Tengah Selatan (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the implementation of Good Governance principles in the administration of Oetuke Village, Kolbano District, South Central Timor Regency. The research employs a qualitative descriptive approach. Data were collected through observation, interviews, and document analysis involving 13 informants, including the village head, village officials, the Village Consultative Body (BPD), traditional leaders, and community members. Data analysis was conducted using the Miles and Huberman model, and data validity was ensured through source triangulation. The results indicate that the Oetuke Village Government has generally implemented Good Governance principles well. Transparency and accountability are reflected through open access to budget information and village activities. Community participation is evident in village meetings and development programs. The principles of rule of law, consensus orientation, and equity have been applied relatively consistently. Furthermore, village development has been carried out effectively and efficiently by utilizing local resources and potential. This study concludes that the implementation of Good Governance in Oetuke Village supports transparent, participatory, and community-oriented village governance.